First report of nematode parasites of Physalaemus santafecinus (Anura: Leiuperidae) from Corrientes, Argentina - Gonzalez, Cynthya Elizabeth (2010)
One hundred and eighty-three nematodes were recovered from 81 adults of leiuperid Physalaemus santafecinus examined from Corrientes, Argentina captured between January 2002 and December 2003. A total of 3 adults nematode species (Cosmocerca podicipinus, Cosmocerca parva, Aplectana hylambatis) and 1 larval species (Physaloptera sp.) were obtained. We present morphological characters, metric information and range for these nematode species and compared these with other specimens collected from different hosts of the Neotropical Realm. This is the first report of nematode parasites of P. santafecinus from Argentina.